Wood Fiber vs Synthetic Thermal Insulation for Roofs Energy Retrofit: A Case Study in Turin, Italy. (March 2017) - Bianco, Lorenza; Pollo, Riccardo; Serra, Valentina
Abstract: In this paper the thermal performance of synthetic and natural insulation materials under real applications are investigated through an experimental activity as well as numerical simulations. During the refurbishment of two houses in Turin (north western Italy) one roof was insulated with a natural material (wood fiber panels) and the other one with a business as usual synthetic material (XPS and polyurethane). An experimental activity was carried out, both during summer and winter seasons, and the results were used to validate a simplified model. During winter, as expected, the strongest influence on the global performance is related to the insulation thickness. As far as the summer season performance is regarded, for smaller roof surfaces, as for the analysed case study, no particular difference was noticed between the two solutions. A better control of the indoor air temperature was evaluated for the wood fiber insulation when applied on a large surface of the roof. In order to define the best cost-benefit retrofit solutions, ad-hoc evaluations need to be performed.